A SOCIOLINGUISTIC ANALYSIS OF TABOO WORDS USED BY THE MAIN CHARACTER IN BAD MOMS MOVIE - Fazri, Saepul; Laili, Elisa Nurul (Teaching English as Foreign Language, Literature and Linguisticss, 2022)
Taboo is something that considered bad and inappropriate or forbidden to do, even the words to be spoken freely in language use. It relates to the rules, ethics, and norms between individual relationships with others in an area or society. Taboo words use is one of disfemism types or a form of human’s expression with use the words that have bad connotations and bad meaning and can hurt the others, people must avoid it with use the more polites words, neutral words or the words can not cause the negative effects or reactions to the others. The author does the research of the taboo words that spoken by the mom’s characters in the Bad Moms movie with a descriptive qualitative approach with use sociolinguistic to understand and make the language as the object. The movie tells about the women who take care of all their works and children without helps from the man or their husband, but one day they feel bored with much works they do and want to escape their responsibilities and regain their freedom and pleasure which have been delayed. The purpose of this study is to identify the types and the functions of the taboo words which spoken by the mom’s characters of the Bad Mom’s movie or the data is taken from the movie’s script. This article tells about the American views of the mom’s character or which categorized bad from their daily speech, specially in taboo words use, because speech or discourse can cause an image self or represent theirself.